CONIFER FOSSIL WOODS FROM THE UPPER CRETACEOUS OF BORORÓ HILL REGION (CHUBUT PROVINCE, ARGENTINA) (Ameghiniana, 2025)
In this study, we examined twelve Upper Cretaceous wood samples collected from the La Rinconada locality, near Bororó Hill in centralArgentine Patagonia. Paleoclimatic inferences were obtained from them, and fungal deterioration was analyzed. All the specimens are conifers, assigned to Podocarpoxylon mazzonii and Brachyoxylon patagonicum. The bearing strata are assigned to the Puesto Manuel Arce Formation (Cenomanian–Turonian?). This wood assemblage, in particular the presence of P. mazzonii, is common in the Campanian–Maastrichtian and there are no older records, which raises questions about the putative age of the Puesto Manuel Arce Formation in this locality. Fungal decay patterns, hyphae, and clusters of resinous tracheids suggest fungus-plant interactions. Based on taxonomic affinities and general growth ring characteristics, a warm and humid climatic scenario is tentatively inferred for the time.